A Conflict’s Impact on Project Goals and Reputation Risk : Lessons from Kosovo Privatization Program - Bach, Karl (World Bank, Washington, DC, 2012)
When designing and implementing a project in a conflict-affected country, some of the conflict's more obvious impacts-damage to infrastructure and energy supplies, are apt to immediately come to mind. However, based on the experiences with the Kosovo privatization program, there are additional problems related to a conflict's aftermath that may be overlooked during a project's design but which should be addressed, and these form the basis for this smart lesson paper.